Limits to responsible innovation. Issue 2 (3rd May 2016) - de Hoop, Evelien; Pols, Auke; Romijn, Henny
ABSTRACT: Responsible Innovation (RI) is a young field of research that has nevertheless had remarkable successes in dissemination within academic and political circles. However, there is relatively little awareness of its limits, blind spots and situations in which it cannot be used for actual innovation trajectories. Without such awareness, there is a risk that RI may get hollowed out and turned into a tool for 'greenwashing'. To examine RI's limits, we present a case study on biofuel innovation in Hassan, South India. This case study demonstrates that there are important barriers that may make it difficult to conduct innovation according to RI values. In particular, we highlight the following factors that emerge from our case study and need more attention in order to be included and adequately theorised in the RI literature: material barriers to innovation, engagement with abandoning or reducing existing practices as a consequence of innovation, power differences and dependencies, (un)clear demarcation of responsibilities, strategic behaviour and, lastly, different, diverging and even contradictory interests. We demonstrate that such factors may obstruct the possibility to innovate in a responsible way, leading us to our core observation that RI should be about innovating responsibly – or not innovating at all.